Tourism and Development in the Senian Context in Aruba: Does It Help or Hurt SIDS? - Don Taylor (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
Tourism development has been a significant factor in the economic growth of Aruba since the closing of its oil refinery in 1986 and the recognition of its status within the Dutch Kingdom. Tourism is the lifeblood of many small island independent states and those categorised as small non-independent jurisdictions (SNIJs), such as Aruba. The question addressed in this paper is whether and how tourism helps or hinders island development. The economic consequences of tourism have been studied in a worldwide perspective; however, we chose to focus on one destination, Aruba, and contextualise our findings by placing them in the context of other Caribbean islands. The reasoning behind this is that tourism is more important to the Caribbean in terms of economic dependence and tourism intensity. Because of the density of tourism in Aruba and its mono-economical development paradigm this makes for an ideal case study.1 Our approach is based on an ontological examination of the relationship between tourism and economic development, which employs a contextualised concept of development that is consistent with Amartya Sen's philosophical position. In that context, prosperity was defined not only in terms of GDP growth, but also in terms of improved social welfare for its citizens, as well as distance from unfreedom in the Senian sense. For the purposes of this paper, the concept of unfreedom is based on the extent to which there is an inertia to shift paradigms, even if the existing paradigm increases vulnerability, fragility, and limits opportunities for its citizens. As a result, despite its economic impact in terms of foreign exchange, investments, and employment, there are significant and pervasive externalities that should be considered when conceptualising tourism's total impact on economic and social development.